078. Malignant Peripheral Nerve Sheath Tumor Masquerading as Neurofibromatosis Type 1 in A 47-Year-Old Female: A Rare Case of Diagnostic Dilemma and Management Challenge - Marpaung, Melissa Saraswaty Eunike; Siregar, Kamal Basri (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical Education, 2024)
Background : Malignant Peripheral Nerve Sheath Tumor (MPNST) is a rare soft tissue sarcoma, often associated with Neurofibromatosis Type 1 (NF1), and can arise from benign neurofibromas. MPNST typically presents with rapidly enlarging masses, pain, or neurological deficits, but can sometimes be mistaken for benign lesions, delaying diagnosis. This case report discusses a 47-year-old female with NF1 whose benign lesion progressed into MPNST. Case: A 47-year-old female presented with a complaint of pus discharge from a lump in her buttock over the past four days. The lump had progressively enlarged for two years before discharging pus. The patient also described multiple lumps on her body since childhood, characteristic of NF1, but noted that only the lump on her buttock had grown significantly and hardened over time. Patient is unable to walk due to her condition since two years ago. Initial histopathological examination indicated benign neurofibroma, but two months later, the patient underwent surgical excision of the tumor as the primary treatment, and the specimen was examined for pathology and showed MPNST. Conclusion: MPNST should always be considered in NF1 patients with rapidly enlarging, firm masses, even when initial pathology indicates a benign process. Timely diagnosis and surgical intervention are critical for optimal outcomes.